Flexural and long term behavior of reinforced concrete beam - Zualkafli, M.I.A (Universiti Malaysia Sarawak, UNIMAS, 2009)
A beam is a member subjected to loads applied transverse to the long dimension, causing the member to bend. This research presents an investigation of flexural and long-term behavior of reinforced concrete beam. It consists of two part of analysis which is theoretical analysis and the experiment study for deflection of reinforced concrete beam. Flexural behavior was investigated through theoretical analysis and experimental study while the long-term behavior was investigated through theoretical study only. In theoretical analysis, the calculation is based on the cracked and uncracked section. Comparison is made between the theoretical and experimental results for the flexural behavior. In long-term behavior deflection, it can be seen that the deflection is about 2.6 times more after six month period. So, it is necessary to consider creep and shrinkage deflection in design.